Academic Senate Minutes 2002-10-31 - Academic Senate:::::::::
Agenda approved. Minutes of 10/3 and 10/17 discussed. Reports from Provost, Vice President of Administration and Finance, APC. Constitutional Amendment and By-laws change regarding Staff Senate Representative – by-laws amended and approved, constitutional vote unopposed. Proposed Resolution on Academic Planning discussed. First Reading of the GE Substitution Policy deferred. First Reading of a modification of the Faculty Emeritus Policy - regarding those in FERP status.